Visceral obesity assessment in type 2 diabetes mellitus using a body shape index may be better as compared to body mass index - Maddodi, Suhas; Gautam, S. K. (International Journal of Advances in Medicine, 2022)
Background: Body mass index (BMI) is being widely used to assess obesity and associated cardiovascular risk but found to be deficient of assessing visceral obesity for which ABSI was developed. Aim and objectives were to determine a body shape index (ABSI) as a better marker than BMI in assessing visceral obesity in type 2 diabetes mellitus (T2DM) patients. Methods: The present cross-sectional study consisted total 150 patients over 40-year age, both male (90) and menopaused female (60). USG was used to measure the visceral obesity. Results: The area under the ROC curve (AUROC) for BMI (kg/m²) predicting V/S fat ratio: >2.5 vs V/S fat ratio: <2.5 was 0.593 (95% CI: 0.5-0.685), thus demonstrating poor diagnostic performance compared to ABSI which was 0.815 (95% CI: 0.748-0.882), thus demonstrating good diagnostic performance. Conclusions: ABSI was better in assessing visceral obesity compared to BMI so can be used along with other markers in assessing cardiovascular risk.